Hyperprogressive disease during nivolumab or irinotecan treatment in patients with advanced gastric cancer. Issue 3 (21st May 2019) - Aoki, Masahiko; Shoji, Hirokazu; Nagashima, Kengo; Imazeki, Hiroshi; Miyamoto, Takahiro; Hirano, Hidekazu; Honma, Yoshitaka; Iwasa, Satoru; Okita, Natsuko; Takashima, Atsuo; Kato, Ken; Higuchi, Kazuhide; et al.
Abstract : Background: Nivolumab showed a survival benefit for advanced gastric cancer (AGC). However, an acceleration of tumour growth during immunotherapy, (hyperprogressive disease, HPD) has been reported in various cancers. This study reviewed the HPD in patients with AGC treated with nivolumab or irinotecan. Methods: The subjects of this retrospective study were patients with AGC with measurable lesions, and their tumour growth rates (TGR) during nivolumab or irinotecan were compared with those during prior therapy. HPD was defined as an increase in TGR more than twofold. Results: 34 and 66 patients received nivolumab and irinotecan in third or later line between June 2009 and September 2018 at our hospital; 22 patients receiving nivolumab had prior treatment with irinotecan, and one patient received irinotecan after nivolumab. Nivolumab and irinotecan showed no differences in disease control rates (38.2% and 34.8%) and in progression-free survival (PFS) (HR 1.1, 95% CI 0.7 to 1.6, p=0.802). The incidence of HPD was slightly higher after nivolumab (29.4%) than after irinotecan (13.5%) (p=0.0656), showing no differences in background between the patients with and without HPD. Compared between HPD and PD other than HPD after nivolumab, the HRs for PFS and overall survival (OS) were 1.1 (95% CI 0.5 to 2.7; p=0.756), and 2.1 (95% CI 0.7 to 5.8; p=0.168), but such clear difference in OS was not observed after irinotecan. Conclusions: HPD was observed more frequently after nivolumab compared with irinotecan, which was associated with a poor prognosis after nivolumab but not so clearly after irinotecan.